2012
DOI: 10.3354/meps09628
|View full text |Cite
|
Sign up to set email alerts
|

Drift algal subsidies to sea urchins in low-productivity habitats

Abstract: Highly productive kelp beds off the coast of Nova Scotia, Canada, export a large quantity of detrital material to adjacent low-productivity habitats. We used a combination of dietary tracers (fatty acids, stable isotopes, and gut contents) and gonad index to evaluate the importance and spatial extent of this energy subsidy to green sea urchins Strongylocentrotus droebachiensis offshore from kelp beds along 240 m transects perpendicular to the shore at 4 sites. Gut contents and δ 13C values indicated the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…Changes in δ 15 N during degradation may obscure interpretation of the tro phic position of consumers in stable isotope analysis of benthic food webs. For example, δ 13 C values in sea urchins collected in barrens up to 240 m from kelp beds indicate that drift kelp is an important food source (Kelly et al 2012). However, these sea urchins have enriched δ 15 N values relative to sea urchins in kelp beds, suggesting either a higher trophic position (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in δ 15 N during degradation may obscure interpretation of the tro phic position of consumers in stable isotope analysis of benthic food webs. For example, δ 13 C values in sea urchins collected in barrens up to 240 m from kelp beds indicate that drift kelp is an important food source (Kelly et al 2012). However, these sea urchins have enriched δ 15 N values relative to sea urchins in kelp beds, suggesting either a higher trophic position (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of detrital kelp production (Krumhansl & Scheibling 2011, Filbee-Dexter & Scheibling 2012 and degradation (Krumhansl & Scheibling 2012b) have been measured in Nova Scotia, however the seasonal variation and extent of detrital deposition to deep subtidal habitats have not been quantified. Kelly et al (2012) found that sea urchins in habitats beyond the kelp bed edge (25 to 30 m depth and 240 m offshore) with access to kelp detritus had higher gonad indices than those living in barrens, but sea urchins at greater depths have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have recorded a decrease in gonad size and fecundity with increasing depth and distance from macroalgal beds for Strongylocentrotus droebachiensis (Keats et al 1984, Bertram & Strathmann 1998, Wahle & Peckham 1999, Brady & Scheibling 2006, Kelly et al 2012) and congeneric species (Rogers-Bennett et al 1995, Wahle & Peckham 1999, Konar & Estes 2003. In contrast, we found that sea urchins at 60 m depth in a sedimentary basin can have comparable or in some cases greater reproductive effort (mean GI at spring or autumn peak: 10 (2009) found that S. franciscanus feeding on macroalgal detritus at 24 m depth also a had similar GI compared to sea urchins in barrens at 6 m depth in the San Juan Islands, Washington, USA.…”
Section: Detrital Kelp Subsidy and Reproductive Condition Of Deep-livmentioning
confidence: 99%
See 2 more Smart Citations